ANTIBACTERIAL ACTIVITY STUDY OF SUPERNATAN OF Lactobacillus acidophilus, Lactobacillus bulgaricus and Lactobacillus casei CULTURE ON RESISTANT BACTERIA - Restiati, Arie
Antibacterial activity test of supernatant of Lactobacillus acidophilus, Lactobacillus bulgaricus, and Lactobacillus casei culture against resistant bacteria had been done. The resistant bacteria used in this study were Pseudomonas aeruginosa Multi Drug Resistants (P. aeruginosa MDR), Methicillin Resistant Staphylococcus aureus (MRSA) and Methicillin Resistant Coagulase Negative Staphylococcus (MRCNS). The antibacterial activity was determined by its value of Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and the equality value to the antibiotic comparator. The results showed that the supernatant of L. acidophilus and L. casei culture had antibacterial activity against P. aeruginosa MDR, MRSA, and MRCNS with MIC value 6.25%, 12.5% and 12.5%, respectively. While the supernatant of L. bulgaricus culture was effective against P. aeruginosa MDR, MRSA, and MRCNS with MIC value respectively 6.25%, 12.5% and 6.25%. MBC value of the three supernatant was twice higher than its MIC value against P. aeruginosa MDR, while against MRSA, MBC value was equal to its MIC value. Different from P. aeruginosa MDR and MRSA, the supernatant of L. acidophilus dan L. casei culture against MRCNS was equal with its MIC value, while supernatant of L. bulgaricus culture had MBC value twice higher than the MIC value. The best combination against P. aeruginosa MDR was demonstrated by 30% supernatant of L. bulgaricus and 70% supernatant of L. casei culture with both MIC and MBC values were 6,25%. From the result of equality test to the antibiotic comparator showed that 50µL of 100% of supernatant of L. acidophilus, L. bulgaricus, and L. casei culture respectively were equivalent to 0.450 µg, 0.347 µg, and 0.350 µg meropenem against P. aeruginosa MDR, and 5.89 µg, 8.56 µg, and 4.57 µg meropenem against MRSA. Furthermore, antibacterial activity of supernatan of L. acidophilus, L. bulgaricus, and L. casei culture were equivalent to 0.0625 µg, 0.0374 µg, and 0.0156 µg tetracycline respectively against MRCNS. In conclusion, supernatan of L. acidophilus, L. bulgaricus, and L. casei culture has antibacterial activity against P. aeruginosa MDR, MRSA, and MRCNS.